2018
DOI: 10.1002/chem.201802086
|View full text |Cite
|
Sign up to set email alerts
|

Helicity Control of Triphenylamine‐Based Supramolecular Polymers: Correlation between Solvent Properties and Helicity in Supramolecular Gels

Abstract: We describe the role of amide groups formed by achiral and chiral moieties to study supramolecular helicity at the molecular level and the correlation between helicity and solvent properties at the supramolecular level. Using circular dichroism (CD) spectroscopy, we observed the CD spectra of supramolecular gel 1, which comprised a triphenylamine (TPA) core, terpyridine, and alanine moieties, formed in various solvents. The strong positive CD signals of supramolecular gel 1 formed in organic solvents, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…In these least polar solvents, the increased favorability of the elongation pathway leads to long fibers, rather than circular polymers. The morphological changes of supramolecular polymers upon changing solvents, highlighted by the above examples, have also been observed in triarylamines, , metallosupramolecular polymers, , azobenzenes, and pyrenes, showing that pathway selection through solvent effects is a general phenomenon in supramolecular polymerizations.…”
Section: Pathway Selection and Morphology Driven By Solvationmentioning
confidence: 70%
“…In these least polar solvents, the increased favorability of the elongation pathway leads to long fibers, rather than circular polymers. The morphological changes of supramolecular polymers upon changing solvents, highlighted by the above examples, have also been observed in triarylamines, , metallosupramolecular polymers, , azobenzenes, and pyrenes, showing that pathway selection through solvent effects is a general phenomenon in supramolecular polymerizations.…”
Section: Pathway Selection and Morphology Driven By Solvationmentioning
confidence: 70%
“…26 Recently, based on the demonstrated helical nature of the TATA stacks, 5 a number of mechanistic studies related to their supramolecular polymerization were published by several research groups. 6,8,23,[27][28][29][30][31] For instance, by adding chiral side chains to the TATA core, Miyajima and Aida demonstrated the possibility to control the M or P helicity of the corresponding supramolecular polymers, and further to fully bias the handedness of a racemate of supramolecular helices made of TATA having no chiral side chains by using only 0.2 mol% of enantiopure TATA (Figure 3B). 6 The control of 500 soldiers by only 1 sergeant represents an unusually strong amplification of chirality attributed to the peculiar dynamics of the TATA propellers.…”
Section: Supramolecular Polymerization Of Triarylamine Tris-amides (T...mentioning
confidence: 99%
“…The sensitivity of chiral TATA derivatives to environmental parameters was also nicely demonstrated by Jung and collaborators, who have revealed correlations between solvent properties and the selective expression of either left-handed or right-handed helicities in organogels. 27 Interestingly, Kim and collaborators published a study in which they observed a full control on the supramolecular chirality of TATA helices by simply using visible circularly polarized light (CPL). 23 Indeed, irradiation of TATA in chlorinated solvents with r-or l-CPL induces their self-assembly with opposite chirality, and moreover the resulting handedness could be totally switched by irradiating with a CPL of the opposite rotational direction (Figure 3C).…”
Section: Supramolecular Polymerization Of Triarylamine Tris-amides (T...mentioning
confidence: 99%
“…The presence of well‐defined bands at 3290 and 1650 cm −1 are characteristic of hydrogen‐bonded N−H and C=O stretching bands, respectively. In addition, their high symmetry suggests a three‐fold helical arrangement of the molecules with intermolecular hydrogen bonds between adjacent TATA cores, as previously described for such compounds in the literature . Above the onset gelation concentration, the morphology of the individual fibers in the physical gel (15 m m in toluene; hereafter referred to as sample A) was found to be similar to those probed from solutions, as observed for instance by SEM imaging of the corresponding aerogel (Figure c).…”
Section: Resultsmentioning
confidence: 81%